De rainha do lar à professora...From a home king to a teacher... (PerCursos, 2007)
O artigo analisa como a representação do magistério foi transformando a escola num local de trabalho para a mulher e o papel da Escola Normal na inauguração do processo de feminização do magistério. Palavras-chave: Feminização do magistério; Escola normalAbstract: The article analysis how the representation of teaching has turned the school into a work place for the woman, and the role of the Escola Normal in the beginning of the process of feminization of the teaching professionKey Word: Feminization of the teaching profession; Normal school.